Comparison of national e‐health implementation in the United States and South Korea. Issue 6 (8th September 2016) - Kim, Kyungdoh; Seok, Hyesung; Proctor, Robert W.
Abstract: With the development of the health care industry, there has been growing recognition that e‐health implementation is needed to improve the efficiency, quality, and safety of care. In addition, a review of previous studies suggests that much can be learned by investigating the difference in national e‐health implementation in the United States and in South Korea. To this end, the main objective of this article is to compare the national e‐health implementation in the case of the United States and South Korea. The results show that in the United States a decentralized e‐health implementation is being followed by individual‐level e‐health. South Korea is pursuing ubiquitous health (u‐health) after a hospital information system and electronic health were implemented. The United States still lags behind many other countries in the implementation of e‐health, possibly due to its low uncertainty avoidance culture. South Korea has been among the frontrunner groups in e‐health implementation as a consequence of its highly developed telecommunication infrastructures and high uncertainty avoidance culture. On the basis of these results, we recommend that establishing health care policies be done on a national scale that takes into account the countries' cultures.